High seebeck coefficient in mixtures of conjugated polymers - Zuo, Guangzheng; Liu, Xianjie; Fahlman, Mats; Kemerink, Martijn (Advanced functional materials, 2018)
A universal method to obtain record-high electronic Seebeck coefficients is demonstrated while preserving reasonable conductivities in doped blends of organic semiconductors through rational design of the density of states (DOSs). A polymer semiconductor with a shallow highest occupied molecular orbital (HOMO) level-poly(3-hexylthiophene) (P3HT) is mixed with materials with a deeper HOMO (PTB7, TQ1) to form binary blends of the type P3HTx:B1-x (0 ≤ x ≤ 1) that is p-type doped by F4TCNQ. For B = PTB7, a Seebeck coefficient S = 1100 µV K−1 with conductivity σ = 0.3 S m−1 at x = 0.10 is achieved, while for B = TQ1, S = 2000 µV K−1 and σ = 0.03 S m−1 at x = 0.05 is found. Kinetic Monte Carlo simulations with parameters based on experiments show good agreement with the experimental results, confirming the intended mechanism. The simulations are used to derive a design rule for parameter tuning. These results can become relevant for low-power, low-cost applications like (providing power to) autonomous sensors, in which a high Seebeck coefficient translates directly to a proportionally reduced number of legs in the thermogenerator, and hence in reduced fabrication cost and complexity.